Monetary policy communication under inflation targeting: Do words speak louder than actions? - Selva Demiralp; Hakan Kara; Pınar Özlü (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This paper assesses the effectiveness of monetary policy communication of the Central Bank of Turkey (CBT) by quantifying the information content of the policy statements released right after the monthly Monetary Policy Committee meetings. First, we quantify the signal regarding the next interest rate decision and ask whether CBT's words match its deeds, i.e., whether communication improves predictability using the Autoregressive Conditional Hazard model. Our findings suggest that the role of statements in predicting the next policy move have strengthened following the adoption of full-fledged inflation targeting (IT) regime. Second, we identify the surprise component of policy communication directly from market commentaries and assess its impact on the term structure of interest rates. We find that the response of the yield curve to policy statements have become highly significant for the unanticipated changes in the monetary policy communication and the relative importance of communication in driving market yields has increased through time.
Keywords: E52; E58; 330; Central Bank Communication; Predictability; Transparency; Inflationssteuerung; Staatliche Information; Informationswert; Türkei